Bilobalide Alleviated Dextran Sulfate Sodium-Induced Experimental Colitis by Inhibiting M1 Macrophage Polarization Through the NF-κB Signaling Pathway - Zhang, Heng; Cao, Nengqi; Yang, Zhilong; Fang, Xingchao; Yang, Xinyu; Li, Hao; Hong, Zhi; Ji, Zhenling (Frontiers in Pharmacology, 2020)
Bilobalide, a unique Ginkgo biloba constituent has attracted significant interest as a novel therapeutic option for neuronal protection . However, there is paucity of data on its effect on colitis. This work sought to evaluate the effect of bilobalide on macrophage polarization in vitro and dextran sulfate sodium (DSS) induced colitis in vivo. Through the MTT and Annexin V/PI assay, it was shown that bilobalide has no significant toxicity on macrophage. Lipopolysaccharide (LPS) and interferon-gamma (IFN-γ) induced macrophage activation and polarization were significantly suppressed by bilobalide as indicated by reduced expression of cytokine, major histocompatibility complex II (MHC-II) and CD11c. Pertinently, the signaling pathway study showed that the phosphorylation of p65 and its nuclear translocation were decreased while STAT1 was not affected. In DSS-treated mice, administration (i.g) of 3 doses of bilobalide namely 1.25 mg/kg (low dose group), 2.5 mg/kg (medium dose group), and 5 mg/kg (high dose group) was performed daily starting from day 1 to day 10. Medium and high dose bilobalide markedly reduced the inflammation of colitis proved via elevation of bodyweight, decrement in disease activity index (DAI), alleviation of colon damage as well as reduction in activity of colon tissue myeloperoxidase activity. In accordance with the in vitro results, the levels of inflammatory cytokines such as interleukin 6 (IL-6), IL-1β and tumor necrosis factor (TNF-α) in serum as well as mRNA expression in colon were obviously reduced in the bilobalide treated groups. Also, factor nuclear factor kappa B (NF-κB) signaling pathway was decreased significantly by bilobalide treatment. Collectively, these results indicated that administration of bilobalide improved experimental colitis via inhibition of M1 macrophage polarization through the NF-κB signaling pathway. Thus, bilobalide could act as a potential drug for the treatment of inflammatory bowel disease (IBD) in the not-too-distant future.